The Role of Energy in the Emergence of Biology from Chemistry - Dibrova, Daria V. (2012)
Any scenario of the transition from chemistry to biology should include an “energy module” because life can exist only when supported by energy flow(s). We addressed the problem of primordial energetics by combining physico-chemical considerations with phylogenomic analysis. We propose that the first replicators could use abiotically formed, exceptionally photostable activated nucleotides both as building blocks and as the main energy source. Nucleoside triphosphates could replace cyclic nucleotides as the principal energy-rich compounds at the stage of the first cells, presumably because the metal chelates of nucleoside triphosphates penetrated membranes much better than the respective metal complexes of nucleoside monophosphates. The ability to exploit natural energy flows for biogenic production of energy-rich molecules could evolve only gradually, after the emergence of sophisticated enzymes and ion-tight membranes. We argue that, in the course of evolution, sodium-dependent membrane energetics preceded the proton-based energetics which evolved independently in bacteria and archaea.